'Diversification: Performance turnaround' (A case of Sarvodaya Hospitals). (August 2014) - Taneja, Sapna; Srivastava, Ravikesh; Ravichandran, N.
<x content-type="archive" xml:space="preserve">Abstract</x> Diversification is a strategic decision that management practises to improve its firm's performance. It continues to be an important strategy for a sustainable corporate growth.1 Corporate diversification has been found to have a curvilinear relation with the corporate performance, i.e. related diversified firms outperform unrelated diversified firms and single business firms.2 Substantiating this concept, the primary purpose of this study is to examine the role of related or with-in industry diversification in the firm's growth. This study shows that diversification has positive impact on financial and organizational performance of Sarvodaya Hospital.